PENGEMBANGAN HUKUM ISLAM KONTEMPORER: DARI QAWLĪ KE MANHAJĪ - Solikhudin, Muhammad (Ahkam: Jurnal Hukum Islam, 2019)
ABSTRACTQawlī approach to solve legal problems, especially contemporary problems, needs to be strengthened and complemented with a manhaji approach. The existence of ushul al-fiqh which have only become supplementary tools to understand the works of classical fiqh, need to be improved to more applicable. Therefore, ushul al-fiqh ul will have direct relevance to the Muslims lives. This paper attempts to offer ushul al-fiqh manhajī which functions to develop the thought of Contemporary Islamic Law. In this paper ushul al-fiqh manhajī will be parsed, departing from classic ushul al-fiqh, the characteristics of ushul al-fiqh manhajī, the contemporary understanding of Islamic law, and the idea of progressive fiqh to face the growing age. It can be understood that ushul al-fiqh manhajī means ushul al-fiqh following the methodology of ulama thought, not the product of their thought. Following the methodology may result in the same or different product. Thinking methodologically means avoiding textuality an sich without studying its philosophical-methodological aspects. In conclusion, ushul al-fiqh manhajī is an offer to develop the thought of Contemporary Islamic Law.Keywords: Ushul al-Fiqh, M anhajī, ContemporaryIslamic law, Qawli